190 Developing effective junior doctor leaders in quality improvement and innovation. (16th November 2020) - Osanlou, Orod; Stanaway, Stephen; Mallon, Lewis; Finlow, Charlie; Rafique, Awais; Metcalf, Phil; Heselden, Emmie
Abstract : Aims: Junior doctors experience a unique breadth of experience due to the nature of their rotational pattern of work. The aim of this work was to engage with, empower and support junior doctors to drive quality improvement (QI) and innovation. Methods: 12 junior doctors were competitively appointed as Wrexham Innovation Fellows by the Site Innovation Lead. They were provided with formal QI and innovation training, mentoring and guidance to drive change. They communicate via whataspp when possible and work together as a group to bring issues to the Site Innovation Lead. This helps to identify barriers, signpost to key players in the organisation, open doors and helps develop a robust PDSA cycle. Results: The Innovation Fellows work as a team and have registered over 20 QI projects to date. 100% (12/12) of Innovation fellows feel that trainee involvement in QI and innovation is a good thing and 92% (11/12) feel that their training has been complimented through their work and support as an Innovation Fellow. Since becoming an Innovation Fellow, 75% (9/12) feel more supported by the organisation to undertake QI and Innovation and 92% (11/12) feel more engaged to undertake QI and innovation since undertaking the programme. The scheme is now expanding to include advanced nurse practitioners, pharmacists and physicians associates. Conclusions: Junior doctors are in unique position to influence innovation, quality improvement (QI) and leadership across NHS organisations. Providing them with bespoke leadership and QI training can help them feel supported, drive innovation, enhance trainee satisfaction, enhance their training and deliver quality improvement and innovation that can help drive change. Other organisations should consider utilising junior doctors and allied healthcare professionals as Innovation Fellows within a structured framework to drive innovation and change.